The effect of multiwall carbon nanotubes in drilling fluids properties [electronic resource] - Dg. Siti Hawa Ag. Bakar, 1992-, author (2015)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2015